PEMBERDAYAAN KADER KESEHATAN TENTANG DIABETES SELF MANAGEMENT DI KECAMATAN TUGU - Prihati, Dyah Restuning; Prasetyorini, Heny (Universitas Widya Husada Semarang, 2024)
Hyperglycaemia causes circulatory obstruction especially in the lower legs. Blockages that appear in the flow of medium or large blood vessels in the legs cause diabetic gangrene. Self-management of diabetes for DM patients includes dietary management, daily activities and exercise, regular medication and avoiding stress. Objective: Community service activities are expected to increase the knowledge of health cadres about diabetes self management. Methods: provision of material on diabetes self management and demonstration of stress management in DM patients with progressive muscle relaxation. Evaluation of activities is carried out by distributing knowledge questionnaires about diabetes self management. Results: PKM participants before being given material about diabetes self management mostly lacked 70% knowledge level. Meanwhile, after being given material about diabetes self management, most of the knowledge levels were good at 90%. The output results include journal publications and publications in online media. Conclusion: Education about diabetes self management can increase the knowledge of cadres in the Tugu District area, besides that it is expected to be able to identify and prevent people who have a risk of DM disease.